Indications for suboptimal low‐dose direct oral anticoagulants for non‐valvular atrial fibrillation patients. Issue 5 (30th June 2017) - Umei, Masahiko; Kishi, Mikio; Sato, Takahiro; Shindo, Akito; Toyoda, Masayuki; Yokoyama, Masaaki; Matsushita, Masashiro; Ohnishi, Satoshi; Yamasaki, Masao
Abstract: Background: Direct oral anticoagulants (DOACs) have been developed for stroke prevention in patients with non‐valvular atrial fibrillation (NVAF). We conducted a retrospective cohort study of patients with NVAF who were newly treated with DOACs in a real‐world clinical setting. Methods: We retrospectively analyzed patients with NVAF newly treated with one of three DOACs—dabigatran, rivaroxaban, or apixaban—between January 1, 2013, and December 31, 2015. Results: A total of 670 patients with NVAF who were newly prescribed one of the three DOACs were analyzed; 74 patients (10.9%) received dabigatran, 290 (43.3%) received rivaroxaban, and 306 (45.8%) received apixaban. Fifteen patients had thromboembolic events, almost half of which were due to discontinuation of DOACs. Six patients had major bleeding, although almost all were discharged with good neurological prognoses. A total of 129 patients were treated with a suboptimal low‐dose DOAC; none experienced a thromboembolic event as long as the DOAC was taken regularly, and none of the patients in any of the three DOAC groups had major bleeding events. Conclusions: With good adherence, the clinical course associated with DOACs is comparatively good. In the future, suboptimal low‐dose DOAC therapy may serve as an appropriate choice for some patients with a high risk of stroke and bleeding.